2023
DOI: 10.1002/agj2.21345
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fertilization impact on hemp (Cannabis sativa L.) crop production: A review

Abstract: Regained interest in hemp cultivation has created opportunities and challenges, especially regarding crop management, for example, fertilizer application rate. Most of the literature on nitrogen (N) management in hemp production is from Asia and Europe, with more established cropping systems than in North America. Through our review, we found evidence that N fertilizer has a noticeable positive impact on basic crop morphology and physiology parameters, or at least the crop responds to such infield fertilizer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 78 publications
(140 reference statements)
0
1
0
Order By: Relevance
“…Moreover, different grain, flower, or fiber hemp production systems may require differing N recommendations based on the final production goal and environmental conditions (Fike, 2016;Kaur et al, 2023). Literature has shown that the N requirement for grain and flower production is higher than fiber production (high N reduces fiber quality) (Fike, 2016;Kaur et al, 2023;Mylavarapu et al, 2020). Therefore, optimizing N fertilization for different economic products obtained from hemp is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, different grain, flower, or fiber hemp production systems may require differing N recommendations based on the final production goal and environmental conditions (Fike, 2016;Kaur et al, 2023). Literature has shown that the N requirement for grain and flower production is higher than fiber production (high N reduces fiber quality) (Fike, 2016;Kaur et al, 2023;Mylavarapu et al, 2020). Therefore, optimizing N fertilization for different economic products obtained from hemp is essential.…”
Section: Introductionmentioning
confidence: 99%
“…According to [19], the acreage harvested for grain and fiber in the United States was estimated at over 24,000 acres, an indication that growers are turning towards scaling up the cultivation of fiber and grain varieties. Despite the resource efficiency of intercropping, there has been limited research on the impact of intercropping hemp, a crop that has resurfaced in the United States as the "new crop on the farm", requiring about 60 and 273 kg ha −1 N fertilizer, contingent on available soil N and weather conditions [20]. This requirement of hemp for nitrogen can be supplemented by cowpea, (Vigna unguiculata L. Walp), a legume crop grown worldwide and capable of fixing about 116 kg N ha −1 N 2 [16,21].…”
Section: Introductionmentioning
confidence: 99%